ROH KUDUS BAGI KARYA KATEKIS - Albert I Ketut Deni Wijaya (Lembaga Penelitian STKIP Widya Yuwana, 2018)
The Holy Spirit is the Spirit of God. By the Holy Spirit, the Church encouraged, built, developed, and has the power to constantly strive to become witnesses of Christ. The Holy Spirit is always present in the entire journey of the Church. He has always worked through a variety of ways. One of the ways the Holy Spirit present in the Church is to call the catechists to participate in the work of the mission that carried the Church. For catechists Holy Spirit plays a role as important as he is present in the Church. The Holy Spirit is believed to be the soul of the Church and souls catechists in carrying out the mission in the world. For catechists, the Holy Spirit to realize that mission work is the work of God; Holy Spirit calling catechists at once become a major force for catechists; The Holy Spirit guides to the truth; and the Holy Spirit giving guidance to the mission of catechists.